Kinetic theory of non-hamiltonian statistical ensembles - Zhukov, A.V.; Cao, J. (Condensed Matter Physics, 2006)
A nonequilibrium statistical operator method is developed for ensembles of particles obeying non-Hamiltonian
equations of motion in classical phase space. The main consequences of non-zero compressibility of phase
space are examined in terms of time-dependent dynamic quantities. The generalized transport equations
involve the phase-space compressibility in a non-trivial way. Our results are useful in molecular dynamics
simulation studies as well as nonequilibrium or quasiclassical approximations of quantum-classical dynamics. Розвинуто метод нерiвноважного статистичного оператора для ансамблiв частинок, якi пiдкоряються негамiльтоновим рiвнянням руху в класичному фазовому просторi. Основнi наслiдки ненульової стисливостi фазового простору вивчаються на мовi часовозалежних динамiчних величин.